2013
DOI: 10.1093/infdis/jit646
|View full text |Cite
|
Sign up to set email alerts
|

Low Antibody Levels to Pregnancy-specific Malaria Antigens and Heightened Cytokine Responses Associated With Severe Malaria in Pregnancy

Abstract: Pregnant women with SM lack pregnancy-specific malaria immunity, and this correlates with heightened inflammatory cytokine concentrations, low haemoglobin levels and high parasite density, suggesting that failure of antibody to control parasitaemia may contribute to SM pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 31 publications
1
31
2
Order By: Relevance
“…This was more marked in the primipara. These observations corroborate previous findings in Africa where high plasma levels of IL-10 were associated with malaria infection during pregnancy (Kabyemela et al, 2008;Nmorsi et al, 2010;Boström et al, 2012;Chandrasiri Upeksha et al, 2013;Chêne et al, 2014). High IL-10 levels have also been reported in mice models during pregnancy malaria (Megnekou et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…This was more marked in the primipara. These observations corroborate previous findings in Africa where high plasma levels of IL-10 were associated with malaria infection during pregnancy (Kabyemela et al, 2008;Nmorsi et al, 2010;Boström et al, 2012;Chandrasiri Upeksha et al, 2013;Chêne et al, 2014). High IL-10 levels have also been reported in mice models during pregnancy malaria (Megnekou et al, 2013).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the maternal peripheral level of IL-17A and the placental and neonate IFN-γ levels were not signi cantly different due to the infection. Several previous studies have shown elevated levels of type 2 anti-in ammatory cytokines IL-10 and IL-4 in the malariainfected group [13,15,23,25,30,31]. Our ndings were different from those reported by Bayoumi et al [11] and Chêne and et al [12] who found higher levels of IL-4 and IL-10 in the non-infected group.…”
Section: Discussioncontrasting
confidence: 99%
“…The roles of IFN-γ and IL-10 in the malaria-infected women with maternal anemia and baby birth weight was controversially documented in a reviewed by Seitz et al [40]. Although Djontu et al [16] reported no signi cant association between IL-6 level, maternal hemoglobin and baby birth weight, an elevated level of IL-6 was associated with anemia in another study [30].…”
Section: Discussionmentioning
confidence: 98%
“…It is unknown if this is attributable to interactions between peripartum exposure to inflammatory cytokines, cardiovascular effects of pulmonary dysmaturity, and placental dysfunction (98100). …”
Section: Resultsmentioning
confidence: 99%